Analysis of Improvement of Distribution Substation Earthing Resistance Values at PT. PLN (Persero) ULP Karebosi - Usrha, Ian Maulana; Gaffar, Ahmad; Sultan, Ahmad Rizal (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
The grounding system at the distribution substation is an essential component closely related to maintaining the reliability of the electrical system. In this regard, this study aims to examine the impact of applying certain grounding methods to improve grounding resistance values at the distribution substation. The research was conducted over five months, from January 15, 2024, to June 15, 2024, at the Pannampu feeder managed by ULP Karebosi. MATLAB GUI was used to theoretically calculate using the Dwight equation related to grounding resistance (Ω) and soil resistivity (Ωm). The results of this study show that the measured grounding resistance values after applying the multiple grounding rod method decreased by 52.49% for the grounding electrode of the lightning arrester GD. KPPKU, 49.45% for the grounding electrode of the transformer body and PHB-TR GD. KPPKU, and 48.94% for the grounding electrode of the lightning arrester GD. KPPDK, which had grounding resistance values of 5.43Ω, 5.44Ω, and 8.42Ω before reconfiguration.